Recognition of dipole-induced electric field in 2D materials for surface-enhanced Raman scattering - Yang, Yuxue; Ao, Shen; Wang, Jiaqi; Fu, Wangyang; Liu, Xiangxuan; Wang, Weipeng (Frontiers in Chemistry, 2023)
The application of two-dimensional (2D) materials, including metallic graphene, semiconducting transition metal dichalcogenides, and insulating hexagonal boron nitride (h-BN) for surface-enhancement Raman spectroscopy has attracted extensive research interest. This article provides a critical overview of the recent developments in surface-enhanced Raman spectroscopy using 2D materials. By re-examining the relationship between the lattice structure and Raman enhancement characteristics, including vibration selectivity and thickness dependence, we highlight the important role of dipoles in the chemical enhancement of 2D materials.